Drawing from life : memory and subjectivity in comic art - Tolmie, Jane (University Press of Mississippi, 2013)
Autobiography has seen enormous expansions and challenges over the past decades. One of these expansions has been in comics, and it is an expansion that pushes back against any postmodern notion of the death of the author/subject, while also demanding new approaches from critics. This is a collection of essays about autobiography, semiautobiography, fictionalized autobiography, memory, and self-narration in sequential art, or comics.